Membrane proteins: molecular dynamics simulations. - Lindahl, E; Sansom, MS (2008)
Molecular dynamics simulations of membrane proteins are making rapid progress, because of new high-resolution structures, advances in computer hardware and atomistic simulation algorithms, and the recent introduction of coarse-grained models for membranes and proteins. In addition to several large ion channel simulations, recent studies have explored how individual amino acids interact with the bilayer or snorkel/anchor to the headgroup region, and it has been possible to calculate water/membrane partition free energies. This has resulted in a view of bilayers as being adaptive rather than purely hydrophobic solvents, with important implications, for example, for interaction between lipids and arginines in the charged S4 helix of voltage-gated ion channels. However, several studies indicate that the typical current simulations fall short of exhaustive sampling, and that even simple protein-membrane interactions require at least ca. 1 micros to fully sample their dynamics. One new way this is being addressed is coarse-grained models that enable mesoscopic simulations on multi-micros scale. These have been used to model interactions, self-assembly and membrane perturbations induced by proteins. While they cannot replace all-atom simulations, they are a potentially useful technique for initial insertion, placement, and low-resolution refinement.